Analisis Kesalahan Berbahasa Bidang Fonologi dan Morfologi pada Cuitan Pengguna Twitter Akun @FiersaBesari - Annisa, Syava Ika; Amalia, Nur (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
As science and technology are now growing rapidly, all information is getting easier to get. Twitter social media is one of the clear evidences of this technological advancement. Twitter can prove its existence so quickly to take the attention of the Indonesian people, especially teenagers through its interesting content and is fairly able to compete with other social media. This study aims to describe language errors in the field of phonology and morphology contained in the tweets of @FiersaBesari twitter accounts. This study uses qualitative descriptive methods and research techniques. The research data in the form of tweets on twitter accounts @FiersaBesari within 3 months. The analysis is carried out by the method of listening and recording which is then presented through the analysis table. In this study, it was found that phonological language errors contained in account tweets @FiersaBesari dominated by non-standard word errors and morphological errors dominated by errors due to morph shortening. Based on the findings of the study shows, that there is still low awareness of the Indonesian people to use good and correct Indonesian on social media Twitter because it has become a characteristic, but it remains a threat to the preservation of Indonesian language.